Patterns of vestibular dysfunction in chronic traumatic brain injury - Taylor, Rachael L.; Wise, Kim J.; Taylor, Denise; Chaudhary, Shikha; Thorne, Peter R. (Frontiers in Neurology, 2022)
Background: Dizziness and imbalance are common following traumatic brain injury (TBI). While these symptoms are often attributed to vestibular dysfunction, the relative contribution of peripheral versus central mechanisms is unclear. This study investigated the prevalence of semicircular canal and otolith abnormalities in a cohort of patients with chronic TBI and symptoms of dizziness or imbalance. The relationship between vestibular, oculomotor and posturography results was further explored. Methods: Clinical records of patients attending the New Zealand Dizziness and Balance Centre from January 2015 to December 2019 were reviewed for consideration in the study. Inclusion required: an age of 18-80 years, a diagnosed TBI, and vestibular assessment using three-dimensional video head impulses (vHIT), cervical and ocular vestibular-evoked myogenic potentials (c and o VEMPs, respectively) and caloric testing. Severe TBI, pre-existing vestibular diagnoses, and incomplete test results were excluded. Rates of abnormalities were determined and compared with results of oculomotor function testing and postural control, measured using the sensory organisation test (SOT). Results: Of 158 reviewed records, 99 patients aged 49 ± 15 years (59 female) fulfilled criteria for inclusion in the study. The median time between the head injury and the clinical assessment was 12 (IQR 6-21) months. Abnormalities involving one or more components of the vestibular labyrinth and/or nerve divisions were identified in 33 of 99 patients (33.3%). The horizontal semicircular canal was most frequently affected (18.2%), followed by the saccule (14.1%), utricle (8.1%), posterior (7.1%) and anterior (2.0%) semicircular canals. Vestibular test abnormalities were associated with skull-base fractures, superior canal dehiscence, and focal ear trauma. Oculomotor dysfunction and postural instability were recorded in 41.1% and 75.5% of patients, respectively. Postural instability correlated with abnormal oculomotor function (p=0.008) but not vestibular hypofunction (p=0.336). Conclusions: Dizziness and/or imbalance in chronic TBI was associated with impaired postural stability for tasks requiring high levels of use of vestibular and visual input for balance. Vestibular hypofunction function identified through vHIT, VEMP and caloric testing was recorded but was less common, except when the injury involved a fractured skull-base. There was no specific pattern of end-organ or nerve involvement which characterised this group of patients.